QUALITY STUDY OF ARABICA COFFEE COMMODITY (Coffea arabica L.) BASED ON SNI COFFEE BEANS No. 01-2907-2008 REVIEWED FROM THE ASPECT OF GOOD AGRICULTURAL PRACTICES (GAP) IN SIMALUNGUN REGENCY - Yenfrida Silitonga; Nurhayati; Muhammad Rizwan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The problem currently faced by Indonesian coffee in the international market is the low quality of coffee generally produced by community plantations. The quality of coffee is still low because post-harvest processing still produces random coffee, namely coffee beans produced with very simple methods and facilities, relatively high water content and still mixed with other ingredients in relatively large quantities. To improve the quality of coffee beans, the application of Good Agricultural Practices (GAP) was chosen as a framework for analyzing coffee quality, because GAP plays a crucial role in ensuring sustainable and quality agricultural practices. This study aims to determine the extent to which GAP is applied to Arabica coffee cultivation in Simalungun Regency and to find out that the application of GAP can improve coffee quality in accordance with the Indonesian Coffee SNI. The research method used is a descriptive method. The basis for selecting the research location was determined intentionally (purposive method) in Simalungun Regency. The sample in this study was coffee farmers totaling 75 respondents. Data analysis was carried out descriptively and multiple linear regression tests. From the results of the study, it can be concluded that coffee farmers in Simalungun Regency have applied GAP in cultivating coffee plants, where the highest GAP application is found in plant varieties with a score of 4.04 and planting coffee at an altitude that is in accordance with a score of 4, while the lowest GAP application is found in harvesting techniques with a score of 3.55, where there are still many farmers who harvest without considering factors that can affect the quality of the coffee beans produced. The water content of coffee beans in Simalungun Regency is around 11.27%. This is in accordance with the SNI 01-2907-2008 standard, namely a maximum water content of 12.5%. The defect value of koi beans in Simalungun Regency is predominantly quality 2, which is 56% and quality 1 is 33.33%. Coffee beans with quality 1 and 2 have good quality. The size of coffee beans in Simalungun Regency is predominantly medium, which is 69.33% and large size is 26.67%. Partially, the application of Good Agricultural Practices, namely plant varieties, coffee land suitability, altitude, fertilization, pest and disease control have a significant effect on the quality of coffee beans, while harvesting techniques do not have a significant effect on the quality of coffee beans. Simultaneously, the application of Good Agricultural Practices (plant varieties, coffee land suitability, altitude, fertilization, pest and disease control and harvesting techniques have a significant effect on the quality of coffee beans.